PENGARUNG PENGGUNAAN APLIKASI WATTPAD TERHADAP PEMAHAMAN MEMBACA TEKS NARATIF SISWA - Siti Yunita Ramadhanti; Nurhaedah Gailea; Sutrisno Sadji Evenddy (Institut Pendidikan Tapanuli Selatan, 2021)
The objective of this research to find out the influence of using Wattpad application on students’ reading comprehension of narrative text. In this research, the researcher used a quantitative method with quasi-experimental design as a method of this research. This research was conducted in two classes ; experimental class and control class. The experimental class was thaught by using Wattpad application and the control class without using it. The sample of this research were X MIA 2 as experimental classs and X MIA 1 as control class, each class consisted 30 students. The data was collected by using test which consisted of try out, pre-test, and post-test. The result of the research showed that using Wattpad application had significant influence toward students’ reading compreheansion in narrative text. It was indicated the value of t-test was higher than value of t-table (9.185 > 2.00) at the level of significant of a 0.05 and degree of freedom is 58. It means that the alternative hypothesis was accepted and null hypothesis was rejected. From those findings, it could be conclude that there was significant influence of using Wattpad application on students’ reading comprehension in narrative text.